Azobenzene: a Visible‐Light Chemical Actinometer for the Characterization of Fluidic Photosystems. Issue 7 (29th June 2021) - Roseau, Mélanie; De Waele, Vincent; Trivelli, Xavier; Cantrelle, Francois Xavier; Penhoat, Maël; Chausset‐Boissarie, Laëtitia
Abstract: ( E )‐Azobenzene is introduced as a suitable chemical actinometer in the visible spectral range (440–540 nm) for photon flux determination of fluidic microphotoreactors or for assessing efficiency of visible light photo‐induced reactions, its evaluation is straightforward without tedious analytics. Photoisomerization quantum yields (Φ E → Z ) of ( E )‐azobenzene were accurately determined upon irradiation at several wavelengths and in different solvents based on well‐known diarylethene. Abstract :